Accounting for the Cost of Interest: Implications for the Timber Industry. - Young, David W. (The Accounting Review, 1976)
This article focuses on the impact changes in accounting procedures for the cost of interest on a firm's finance, with assessing implications of these changes in accounting procedures for three firms in the timber industry: Weyerhaeuser Co., Georgia-Pacific Corp., and Boise Cascade Corp. Because adequate data on new construction financing were not available, the analysis of the three companies, considering the proposed changes in accounting procedures, was confined to the following areas: the identification and used of an interest charge for shareholders' equity; computation of changes in the value of timberland inventory over a period of about 20-25 years and the corresponding changes in common shareholders' equity; and determination of changes in net income over the same period resulting from a higher value of depletion and the use of an interest charge for plant and equipment involved in the production process. On analysis, it was noticed that the effect of the changes was substantial. The reported value of the timberland account increased by more than 80 percent for Weyerhaeuser and by approximately 50 percent for the other two companies. Retained earnings increased by 17 percent in Boise Cascade, 30 percent in Weyerhaeuser and 60 percent in Georgia Pacific. Net income for the period studied was reduced considerably for each firm, actually becoming a loss for Boise Cascade.